Rehabilitation of the esthetic zone using multiple adjacent individual implant-supported restorations: where are the limits? - Bernal-Dulcey, Guillermo; Murgueitio, Rafael; Ríos, Héctor Fabio (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Rehabilitation of the partially edentulous anterior maxilla is considered one of the most difficult challenges for the restorative dentist due to the esthetic, functional and psychological implications. Implant-supported restorations provide an appealing treatment alternative that responds to today’s patient expectations. The gold standard for this scenario has been the use of an implant-supported fixed partial denture with pontics that masks the soft tissue deficiencies, with acceptable esthetic results. However, nowadays patients are looking for individual single crowns since they believe that this type of restorations resemble the natural dentition, are easy to clean and floss. From the dentist perspective, they are easy to maintain and in case of prosthetic complications they can be repaired or changed without compromising the adjacent restorations. Three parameters have been identified that could guide the decision-making process when multiple adjacent implant supported restorations (MAISR) are selected as the treatment of choice: 1) Smile line 2) Inter-implant distance and tooth-implant distance 3) Patient's expectations and ability to clean.